2000
DOI: 10.1007/bf03170483
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Infant Death Syndrome — are parents getting the message?

Abstract: Future programmes should target first time parents, should provide clear information regarding appropriate infant thermal environment, and should ensure regular updating of medical personnel so that they can instruct families on best current practice. Smoking remains a significant health issue with an impact on sudden infant death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…More first-time parents responded to this survey. Decisions families make in caring for their first child will often provide the foundations for future infant care practices and sleeping behaviours employed with subsequent children [33][34][35]. Therefore, where practices differ from current guidelines, this may indicate an underestimate of practices utilised by families in the broader population.…”
Section: Discussionmentioning
confidence: 99%
“…More first-time parents responded to this survey. Decisions families make in caring for their first child will often provide the foundations for future infant care practices and sleeping behaviours employed with subsequent children [33][34][35]. Therefore, where practices differ from current guidelines, this may indicate an underestimate of practices utilised by families in the broader population.…”
Section: Discussionmentioning
confidence: 99%
“…Although co-sleeping is customary in more than 100 cultures (Latz, Wolf, & Lozoff, 1999), it is not so in the United States and certain other countries, such as Ireland (Cullen et al, 2000). In a sample of 150 children under 4 years of age, Lozoff and her colleagues found that 35% of White and 70% of Black children were co-sleeping at least twice per month (Lozoff, Wolf, & Davis, 1985).…”
mentioning
confidence: 99%
“…A study investigating practices among population groups internationally demonstrated that families in Hungary (0%), Scotland (4%), Canada (8%) and NZ (9%) reported the lowest incidence of pillow use, with the Chinese sample groups (Hong Kong 80%, Beijing 95% and Chongqing 95%) reporting the highest prevalence [108]. Other studies exploring the use of pillows within an infant's sleep space reported a prevalence of 14% among an Australian sample [16]; 18% among a UK sample [12]; 19% in an Iranian sample [17]; 21% among an Irish sample [65]; 64% among a Mexican sample [96]; 66% among a UAE sample [36]; 77.3% among a Turkish sample [146]. In a recent Croatian study [45], it was found that 86% of infants slept with a pillow or stuffed toy, whereas in a US study [139], 14% were reported to place their infants to sleep sometimes or always with cot bumpers, pillows or blankets.…”
Section: Items In An Infant's Sleeping Spacementioning
confidence: 99%
“…The proportion of infants who sleep in the same room as their parents or an adult caregiver but did not share a sleep surface (i.e., sleep in their own infant bed) was not always clearly measured or reported. Many papers reporting room-sharing prevalence also included infants who usually bed-shared [20,21,23,45,48,65,72,81,83,135]. Möllborg et al [104] reported that within a Swedish cohort, 65.7% of infants slept in their own separate bed in the parent's room.…”
Section: Infant Sleep Location: Room-sharing and Surface Sharingmentioning
confidence: 99%